Surgical Margins for Ameloblastoma in Dogs: A Review With an Emphasis on the Future - Goldschmidt, Stephanie (Frontiers in Veterinary Science, 2022)
Ameloblastoma is a benign epithelial odontogenic tumor with the capacity to aggressively invade the surrounding bone. Surgical removal of the tumor can result in extended disease-free interval (cure). However, controversy surrounds the most appropriate surgical margin required to prevent local recurrence while simultaneously minimizing morbidity. En bloc excisional surgery carries the risk of major complications such as mandibular drift, hemorrhage, and oronasal fistula formation. Conservative therapy without a safety margin reduces potential morbidity but is likely to result in local recurrence. No reliable rate, nor time to recurrence, is documented but may be as high as 91% with conservative therapy. Conversely, surgery with a 10- to 20-mm margin is associated with a 0–4.6% recurrence rate. There is no documented difference in the recurrence rate with a 10- vs. 20-mm margin. The correlation of the histologic margin with the recurrence rate following excisional surgery has not determined a required histologic safety margin. Rather, no local recurrence occurs despite narrow or incomplete margins. Thus, pathologic margins > 0 mm may be sufficient to prevent local recurrence or recurrence may be protracted. Accordingly, a narrow (5–10 mm) gross surgical margin may be the most appropriate. Additional research is required for confirmation, and only level 4 evidence on safety margins has been achieved thus far. Future work should focus on defining the extension of neoplastic cells past the demarcation of ameloblastoma on variable diagnostic imaging modalities as well as determining the recurrence rate with various surgical and histologic safety margins.